Chemical Capture and Sensing of Bovine Serum Albumin with Phenothiazinylcarbaldehyde-Labeled 2′-Deoxyuridine - Sahu, Rajesh; Sanghvi, Yogesh S.; Gunturu, Krishna Chaitanya; Bag, Subhendu; Kapdi, Anant R. (Synlett, 2024)
Chemical-capture-mediated sensing has had a great impact on proteomic research. Toward this end, we demonstrate the chemical trapping of BSA by the reactive formyl functionality of a newly developed fluorescent nucleoside probe, formylphenothiazine-labeled-2′-deoxyuridine. The probe is capable of trapping BSA via Schiff base formation leading to fluorescence ‘switch-on’ sensing with a large hypsochromic shift of ca. 100 nm. The α-amylase does not show any significant change in fluorescence response, demonstrating the efficiency of the probe in selective sensing of BSA. Docking studies suggest the preferential interaction of the phenothiazinylcarbaldehyde-labeled dU with the residual amino acids in site I of the BSA protein as compared to site II.
Keywords: formylphenothiazine-labeled 2′-deoxyuridine; chemical capture; Schiff base; fluorimetric sensing; bovine serum albumin; molecular docking